A Review of Additives on (Co-)Stabilization of Phosphorus and Heavy Metals during Thermal Processing of Sewage Sludge - LI Haofei; QIN Yuhong; DU Yujia; LI Wanyao (Taiyuan Ligong Daxue xuebao)
[Purposes] Sewage sludge is considered as a “substitute mine” for phosphorus, and thermal processing is an important means for its resource utilization and harmless treatment. Through summarizing the simultaneous stabilization of phosphorus and heavy metals with various additives during the thermal treatment of sludge, the simultaneous solidification mechanism of calcium-based additives for phosphorus and heavy metals is elucidated in this review. [Methods] The migration and transformation laws of phosphorus and heavy metals in thermal processes such as incineration, pyrolysis, gasification, and hydrothermal carbonization are summarized, and the impact mechanisms of calcium-, magnesium-, and chloride-based additives on the stabilization of phosphorus and heavy metals are generalized. It is noted that the addition of CaO promotes the conversion of non-apatite inorganic phosphorus to apatite inorganic phosphorus, improves the availability of phosphorus, and achieves co-stabilization of heavy metals. [Findings] Exploring the co-stabilization of CaO on phosphorus and heavy metals during sludge gasification, as well as the interaction mechanism between the three during gasification, is one of the future research directions.